PEMANFAATAN TUMBUHAN OBAT BAGI IBU SEBELUM DAN SESUDAH MELAHIRKAN PADA MASYARAKAT SUKU MELAYU DI DESA SEKURA KABUPATEN SAMBAS - Peli, Peli; Linda, Riza; Wardoyo, Elvi Rusmiyanto Pancaning (Universitas Tanjungpura, 2020)
The Malay people stilluse various types of plants as traditional medicine for the treatment of mothers before and after childbirth.The purpose of this study is to find out the types and parts of plants that are most widely used for the treatment of mothers before and after childbirth. This research was conducted from September to December 2020 in Sekura Village Sambas Regency. Determination of respondents using purposive sampling method. The results of the study obtained 38 types of plants classified in 21 families. The most widely used family is the family Zingiberaceae at 13%. Prenatal treatment is done pregnant 7 months until the end of the process of childbirth, namely drinking potions and pregnant bath ingredients. Traditional postnatal medicine is carried out for 44 days consisting of internal and external medication. The internal medication consists of herbs, sireh untalan, and sambal lade. The external medication consists of abdominal param, body param, bathing material and massage oil. These traditional drugs were taped, eaten, drink and applied as an ingredient for bathing. The most plant part in medicine is the leaves by 27% and the least is the stem by 2%.